EVALUASI SISTEM INFORMASI AKUNTANSI ATAS PROSEDUR PENERIMAAN & PENGELUARAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SEKOLAH MENENGAH PERTAMA NEGERI 2 ANDONG BOYOLALI - Destina Sari, Endang Masitoh W. (ITB AAS INDONESIA, 2017)
The research had purpose for evaluation accounting information sytem on procedure revenue and expenditure BOS in SMP Negeri 2 Andong. The population in this study is the procedure Revenues and Expenditures of School Operational Funds (BOS). Accounting Information Systems can be used as an internal control. The method in this research is descriptive qualitative by using the process of triangulation to measure the suitability of the data by interview, observation and literature. Results from the study show that there are accounting information systems at the school and the line of separation of duties has not been effective.Keyword : Accounting Information Systems, Cash Revenue, Cash Expenditures, School Operational Assistance Fund (BOS)